Pilot study for the evaluation of safety profile of a potential inhibitor of SARS-CoV-2 endocytosis - Paolacci, Stefano; Ceccarini, Maria Rachele; Codini, Michela; Manara, Elena; Tezzele, Silvia; Percio, Marcella; Capodicasa, Natale; Kroni, Dorela; Dundar, Munis; Ergoren, Mahmut Cerkez; Sanlidag, Tamer; Beccari, Tommaso; et al. (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the current pandemics of coronavirus disease. This virus is able to attack the cells of the airway epithelium by binding to the transmembrane angiotensin I converting enzyme 2 (ACE2). We developed an oral spray that could inhibit the SARS-CoV-2 endocytosis. The spray contains hydroxytyrosol for its anti-viral, anti-inflammatory and anti-oxidant properties, and α-cyclodextrin for its ability to deplete sphingolipids, that form the lipid rafts where ACE2 localizes. The aim of the present pilot multi-centric open non-controlled observational study was to evaluate the safety profile of the “Endovir Stop” spray. Methods: An MTT test was performed to evaluate cytotoxicity of the spray in two human cell lines. An oxygen radical absorbance capacity assay was performed to evaluate the antioxidant capacity of the spray. The spray was also tested on 87 healthy subjects on a voluntary basis. Results: The MTT test revealed that the spray is not cytotoxic. The ORAC assay showed a good antioxidant capacity for the spray. Endovir Stop tested on healthy volunteers showed the total absence of side effects and drug interactions during the treatment. Conclusions: We demonstrated that Endovir Stop spray is safe. The next step would be the administration of the efficacy of the spray by testing it to a wider range of people and see whether there is a reduced infection rate of SARS-CoV-2 in the treated subjects than in the non-treated individuals.